Problems of Determining the Cost of Collateral in the Conditions of Implementation Basel II, III Standards in Russia - Fedotova, Marina A.; Tazikhina, Tatiana V.; Nadezhdina, Yana V.; Raeva, Inna V. (Journal of Reviews on Global Economics, 2018)
This paper analyzes the impact of the collateral value on the assessment of credit risk in the framework of the Advanced IRB approach and proves its impact on the LGD parameter and also provides a statistical analysis of the linear and multifactor models of the LGD score in order to detect a positive correlation. Based on the analysis, factors that influence the cost of collateral and the valuation of LGD are determined. The results of the research confirm the hypothesis put forward in the study that the valuation of collateral provides a significant influence on the measurement and management of the LGD indicator in conditions of building an Advanced IRB approach